Effect of sowing windows on growth and yield of groundnut (Arachis hypogaea L.) genotypes: EFFECT OF SOWING WINDOWS ON GROWTH AND YIELD OF GROUNDNUT GENOTYPES RESULTS AND DISCUSSION - K RAAGAVALLI,; T M SOUMYA,; H K VEERANNA,; S P NATARAJU,; H NARAYANSWAMY, (Journal of Oilseeds Research, 2019)
In general, groundnut crop is subjected to varied climatic conditions and monsoon vagaries in particular, as it is mostly grown under rainfed conditions during kharif. It is necessary to select a suitable groundnut genotype and sowing window as a non-monetary input to reduce the effect of climate on crop yield. Field experiment was conducted at AHRS, Bavikere, UAHS, Shivamogga, to study the influence of sowing windows on growth and yield of groundnut genotypes under rainfed conditions during kharif, 2017 in sandy loam soil. Four groundnut genotypes viz., GKVK-5, GPBD-4, G2-52 and TMV-2 and four sowing windows viz., II fortnight of June, I and II fortnights of July and I fortnight of August were selected. The experiment was laid out in Randomized Block Design with factorial concept using two factors, each with four levels replicated thrice. The experimental results revealed that, the genotype GKVK-5 recorded significantly higher pod yield (16.73 q/ha), shelling percentage and kernel yield, followed by G2-52, GPBD-4 and TMV-2. While, the crop sown during II fortnight of June recorded significantly higher pod yield, shelling percentage and kernel yield compared to other sowing windows, due to increased crop growth parameters. Delayed sowings reduced crop growth and development due to moisture stress, thereby, decreasing the pod yield. However, among the treatment combinations, genotype GKVK-5 sown during II fortnight of June recorded higher pod yield (18.07 q/ha).